THE RELATION OF PERSONAL HYGIENE WITH THE RISK OF OCCURRENCE OF SOIL-TRANSMITTED HELMINTH CO-INFECTION IN TB PATIENTS IN THE WORKING AREA OF THE JENGGAWAH HEALTH CENTER IN JEMBER REGENCY - Ellen Ocktavironita; Bagus Hermansyah; Angga Mardro Raharjo; Diana Chusna Mufida; Dini Agustina; Muhammad Ali Shodikin (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Tuberculosis (TB) and soil-transmitted helminth (STH) infections are infectious diseases with a high prevalence in Indonesia. STH co-infection in TB patients can worsen the prognosis of TB disease due to the dysregulation of the immune response. The high prevalence of STH infections in Indonesia is caused by environmental factors such as poor personal hygiene habits. Jenggawah Subdistrict is an area with a high number of TB cases in Jember Regency and most of the area is in the form of agricultural fields and plantations that have a suitable humidity and temperature for the development of STH. The purpose of this study was to determine the relationship of personal hygiene risk factors with the risk of STH co-infection in TB patients in the work area of the Jenggawah Health Center in Jember Regency. This study used an observational analytic design with a cross sectional method and was conducted from September to December 2019. The research was conducted at the TB Polyclinic in Jenggawah Health Center in Jember Regency with a total sample of 26 respondents who were given a personal hygiene questionnaire. Stool examination was conducted at the Laboratory of Parasitology FK UNEJ using sedimentation and flotation methods. The results showed the incidence of STH co-infections was 15.3%, good personal hygiene was 57.7%, and bad personal hygiene was 42.3%. Fisher exact test results showed that there was no significant relationship between personal hygiene risk factors and the risk of the occurrence of STH co-infection in TB patients in the working area of the Jenggawah Health Center in Jember Regency (p = 1,000).